Sounds of Synthesis: Acoustic Real‐Time Analysis of Laser‐Induced Graphene. (13th January 2022) - Li, Victor D.; Li, John T.; Beckham, Jacob L.; Chen, Weiyin; Deng, Bing; Luong, Duy X.; Kittrell, Carter; Tour, James M.
Abstract: Laser‐induced graphene (LIG) can be patterned on a variety of substrates using a laser scriber/cutter. The quality and morphology of LIG is currently analyzed using Raman spectroscopy and electron microscopy. Here a method is presented to enable analysis of LIG in real‐time during the synthesis using a microphone attached to the laser writing head, followed by a simple acoustic signal processing scheme. It is demonstrated that it is possible to use the same energy input to simultaneously drive the conversion process and probe the formation of LIG in situ by applying Fourier and integral analyses, thus allowing rapid, high‐throughput determination of the local quality and morphology of the produced LIG. Abstract : Laser‐induced graphene can be formed using a commercial laser cutter. The material properties vary, and current methods of characterization involve microscopy. It is demonstrated that the sounds can be collected in situ using a microphone and analyzed to characterize the product. Analogous methods may be extended to other materials synthesis and processing techniques in the future.